2006
DOI: 10.2527/jas.2005-625
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ovine maternal temperature, and serum cortisol and interleukin-6 concentrations after challenge with Escherichia coli lipopolysaccharide during pregnancy and early lactation1

Abstract: Major changes in maternal physiology during pregnancy and lactation can have a large impact on the immune and neuroendocrine systems. One of the most significant changes, observed in rats and mice, is hyporesponsiveness of the hypothalamic pituitary adrenal axis (HPAA) in response to inflammation, restraint, and other psychological stressors during late pregnancy and lactation. This attenuation, however, has not been well characterized in ruminant animals and may be relevant to their susceptibility to inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
19
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 30 publications
3
19
1
Order By: Relevance
“…First, it is possible that the LPS challenge dose used in the present study was too high to detect subtle changes in neuroendocrine function in sheep, as we have historically used a challenge dose of 400 ng/kg as opposed to 1.2 g/kg to assess their neuroendocrine function (Kabaroff, 2006a); the rationale for choosing this LPS dose was that it had to induce fetal stress in order to examine the protective effects of FM supplementation on fetal programming, and a previous study performed by our group demonstrated that this dose induced fetal stress and affected programming of the ovine hypothalamic-pituitaryadrenal axis . Second, it has been previously demonstrated that sheep are hyperadrenal cortisol responsive to LPS during this stage of pregnancy, possibly due to fetal cortisol secretion (Kabaroff et al, 2006b). Given this, it is also possible that FM supplementation was not sufficient to attenuate the combined effects of maternal and fetal ACTH and cortisol secretion.…”
Section: Discussionmentioning
confidence: 90%
“…First, it is possible that the LPS challenge dose used in the present study was too high to detect subtle changes in neuroendocrine function in sheep, as we have historically used a challenge dose of 400 ng/kg as opposed to 1.2 g/kg to assess their neuroendocrine function (Kabaroff, 2006a); the rationale for choosing this LPS dose was that it had to induce fetal stress in order to examine the protective effects of FM supplementation on fetal programming, and a previous study performed by our group demonstrated that this dose induced fetal stress and affected programming of the ovine hypothalamic-pituitaryadrenal axis . Second, it has been previously demonstrated that sheep are hyperadrenal cortisol responsive to LPS during this stage of pregnancy, possibly due to fetal cortisol secretion (Kabaroff et al, 2006b). Given this, it is also possible that FM supplementation was not sufficient to attenuate the combined effects of maternal and fetal ACTH and cortisol secretion.…”
Section: Discussionmentioning
confidence: 90%
“…with Streptococcus pyogenes peptidoglycan on d 5 after mating, increased concentrations of cortisol in a biphasic pattern were observed [21]; although in the low dose S. pyogenes peptidoglycan group pregnancy was maintained even though fever was induced and concentrations of cortisol were elevated [21]. An increase in concentrations of cortisol as a result of immune system interactions (direct and/or indirect) in concert with physiological stress to the animal is a typical response; as has been observed previously during pregnancy toxemia in the ewe [12] and following LPS exposure in the pregnant ewe [13] and fetus of the pregnant ewe [22]. Again, it is not clear why serum concentrations of cortisol differed between bacterial-inoculated ewes and Controls in Experiment 1 but not in Experiment 2.…”
mentioning
confidence: 63%
“…However we cannot rule out that placement of the inoculum, E. coli serovar, plasmid effects or that a combination did not influence the progression of infection and induction of a differential immune response between the two studies. As an elevation in serum concentrations of cortisol in response to an infection of the type reported here is characteristic (see Experiment 1 in this study, and refs [12,13,21,22]), this requires further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, studies on lactating rats revealed elevated basal secretion of adrenocorticotropic hormone (ACTH) and corticosterone, with a flattened diurnal rhythm for corticosterone secretion (Windle et al 2013). However, no changes in basal cortisol secretion have been observed in lactating sheep (Kabaroff et al 2006;Tilbrook et al 2006).…”
mentioning
confidence: 99%